Perception and practices of COVID appropriate behavior: A cross-sectional study among adult populations in rural and urban West Bengal - Archita Bhattacharya; Manisha Das; Santanu Ghosh; Amrita Samanta (Acta Medica International, 2022)
Introduction: Recent COVID-19 pandemic is an unprecedented public health problem worldwide. Knowledge about the disease and adoption of COVID Appropriate Behavior (CAB) are of utmost importance in combating the pandemic. The study was conducted to assess and compare the knowledge, attitude, and practice and to determine different misconceptions and wrong practices related to the disease among urban and rural populations. Materials and Methods: A community-based analytical study with cross-sectional design was conducted from January 2021 to March 2021 among 144 adult residents from urban and rural West Bengal. Multistage sampling was adopted and a predesigned, pretested, semistructured schedule was used for interviewing study subjects. Results: Urban people were significantly more knowledgeable and more appropriate in attitude and practice than rural people (P < 0.05). The mean knowledge and attitude scores of urban population were significantly higher than the rural population across age groups, gender, occupation, and education (P < 0.05), whereas mean practice score was significantly higher across gender and occupation in the urban population compared to the rural population (P < 0.05). Many cultural and indigenous practices such as drinking warm water, using mouth wash, using home remedies were more common in urban areas and consumption of homeopathy medicines, lighting candles, making sound with utensils, blowing conch shells, and worshipping corona were observed more in rural areas. Conclusions: Wide gap exists in knowledge, attitude, and practice between urban and rural population and there were many wrong perceptions and practices surrounding COVID-19 among both urban and rural population. Appropriate policy for improving knowledge, attitude, and CAB is the need of the hour.